2004
DOI: 10.1152/physiolgenomics.00057.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac transcriptional response to acute and chronic angiotensin II treatments

Abstract: Exposure of experimental animals to increased angiotensin II (ANG II) induces hypertension associated with cardiac hypertrophy, inflammation, and myocardial necrosis and fibrosis. Some of the most effective antihypertensive treatments are those that antagonize ANG II. We investigated cardiac gene expression in response to acute (24 h) and chronic (14 day) infusion of ANG II in mice; 24-h treatment induces hypertension, and 14-day treatment induces hypertension and extensive cardiac hypertrophy and necrosis. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 77 publications
8
58
0
Order By: Relevance
“…dling, and intracellular signaling, observed in experimental models of heart failure induced by pressure overload (32), genetic modifications (8, 32), or drug treatments (12,25,26), suggesting the existence of a common basic mechanism underlying the various aspects of cardiac remodeling in response to different initiating insults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dling, and intracellular signaling, observed in experimental models of heart failure induced by pressure overload (32), genetic modifications (8, 32), or drug treatments (12,25,26), suggesting the existence of a common basic mechanism underlying the various aspects of cardiac remodeling in response to different initiating insults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus simultaneous evaluation of 4,000 genes by the use of microarray technology to query the quantitative changes in left ventricular RNA in response to ANG II-induced progression, and, subsequently, regression of cardiac hypertrophy, revealed a set of genes previously not known to be associated with cardiac hypertrophy (12). Recently, a comprehensive analysis of the cardiac transcriptional response to acute and chronic ANG II treatments has been carried out using microarrays containing 22,000 unique transcript probes (26). One limitation of the microarray technology, however, is its dependence on the genes annotated to date.…”
mentioning
confidence: 99%
“…The mechanism(s) leading to the marked capillary growth in response to ANG II-induced myocardial hypertrophy in FGF2-deficient mice remains to be elucidated. It is of note, however, that in a recent study on the cardiac transcriptional response to acute and chronic ANG II treatment in mice Larkin et al 46 found that the response to ANG II infusion in mice is somewhat inconsistent and in general not as marked as in rats. After acute ANG II infusions an increase in blood pressure and related changes in myocardial gene expression, but not in heart weight, was found.…”
Section: Discussionmentioning
confidence: 96%
“…After acute ANG II infusions an increase in blood pressure and related changes in myocardial gene expression, but not in heart weight, was found. 46 Among the genes differently expressed It seems very unlikely that the physiological role of FGF2 in the adult organism would be inhibition of adaptive capillary growth. Thus, in the absence of FGF2 other growth factors may be upregulated which take over the role normally played by FGF2, thus facilitating capillary growth.…”
Section: Discussionmentioning
confidence: 99%
“…A second example of the manner in which we have used data-integration to infer biological meaning is the analysis of a mouse model of hypertension analysed by Jennie Larkin and members of our group in collaboration with Haralambos Gavras of Boston University (Larkin et al 2004). Hypertension is a significant disease affecting one in four Americans and is strongly associated with heart disease, the number one cause of death in the United States.…”
Section: Extracting Meaning Using Go-term Meta-analysismentioning
confidence: 99%